Vida y muerte en el pensamiento indígena iku (arhuaco) - Ginna Marcela Rivera Rodríguez (Antípoda: Revista de Antropología y Arqueología)
This article explores the understanding of life and death among the Iku (Arhuaco) Indigenous people of the Sierra Nevada de Santa Marta, in northern Colombia. The content presents the findings of research conducted within the Indigenous territory from 2018 to 2020, which facilitated an exploration of the conceptions, material and spiritual practices that the Arhuacos engage in daily around these two concepts. Through ethnographic work and a review of anthropological literature on the Sierra Nevada, the article exposes what I propose to understand as Iku vitality, a notion that expresses the intrinsic connection between materiality and spirituality in the Arhuaco worldview. This connection has a particular continuity with the concept of death and, through experiences in the territory, takes on different expressions that can be interpreted systematically through ethnographic coexistence and various cultural practices employed by the Arhuaco people for the ritual and social management of material loss. This work follows methodological and epistemological principles of an anthropology that, in contexts of death and violence, is dedicated to listening, understanding, and highlighting local interpretations that emerge as comprehensive factors of life’s fractures, as well as the forms, times, spaces, and social resources available to confront and reconstruct them.